Sirenomelia (mermaid baby) - Rengaraj, Nithya; Annal, Anjana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Sirenomelia is a rare congenital malformation wherein the two lower limbs are fused to give an appearance of a mermaid. It is almost always lethal and is associated with several other defects like anorectal malformations, renal agenesis, umbilical cord vessel abnormalities and gastrointestinal defects. Reporting this case of sirenomelia from our institution in a preterm baby born alive to a primigravida at 36 weeks of gestation, who presented in labour.